Caseworker's Discretion and the Effectiveness of Welfare-to-Work Programs - Jonneke Bolhaar; Nadine Ketel; Bas van der Klaauw (Institute of Labor Economics (IZA), 2018)
In this paper we focus on the role of caseworkers in the assignment and take-up of welfare-to-work programs. We conduct a field experiment that generates exogenous variation in the assignment to different policy regimes to caseworkers. The experiment allows us to provide evidence on the effectiveness of welfare-to-work programs and to study how caseworkers exploit their discretion in assigning these programs to welfare recipients. We find substantial heterogeneity in how caseworkers assign welfare-to-work programs. Participation in the experiment and learning about the effectiveness of the different programs does not induce caseworkers to focus more on the effective programs. This implies that obtaining knowledge about welfare-to-work programs is not enough to improve policy, also effort on implementation is required.
Keywords: C93; I38; J64; J08; 330; field experiment; welfare-to-work; caseworkers